DEVELOPING COMMUNICATION SKILLS IN THE PROCESS OF TEACHING ENGLISH TO YOUNG LEARNERS AT SECONDARY SCHOOLS - Minavvarova Xidoyatxon Azizxo’ja qizi; Makhsudova Oysara (Modern American Journals, 2025)
This article explores effective pedagogical strategies for developing communication skills in English among young learners at secondary schools. The ability to communicate fluently and confidently is one of the fundamental goals of modern language education, especially in today’s globalized world where English serves as a bridge across cultures. The study emphasizes the importance of integrating communicative competence into the language teaching process from an early stage, using learner-centered and interactive approaches. Grounded in communicative language teaching (CLT) principles and sociocultural theory, the article examines how interactive methods—such as role plays, group discussions, think-pair-share tasks, and project-based learning—can enhance students' speaking and listening abilities. Special attention is also given to the incorporation of technology through tools like Kahoot and Quizlet, which were shown to increase learner engagement, motivation, and active participation in real-time communication scenarios. The research involved classroom observations and the implementation of selected interactive methods in English lessons with secondary school learners.
Keywords: Communicative competence, young learners, secondary school, interactive methods, English language teaching, communication skills, technology integration, CLT, learner-centered approach, classroom interaction.